Factors Influencing Adoption of E-Commerce Innovation among Village Employees - Nur Hadian; Muhammad Rizaludin (G-Tech: Jurnal Teknologi Terapan, 2024)
This research investigates the factors that affect the adoption of e-commerce innovations by village government employees, who are crucial in developing village-owned enterprises (BUMDES). The study uses a literature review to explore the factors influencing the adoption of e-commerce by village employees. By searching for articles published between 2014 and 2023 in reputable journals like Scopus, EmeraldInsight, Science Direct, and EBSCOhost, 30 relevant articles were obtained. The research reveals that technological, economic, environmental, organisational, and trust factors have the greatest impact on the adoption of e-commerce in village governments. These findings can serve as a basis for future research on the effectiveness of these factors and can also assist policy makers and organizations in implementing effective strategies for e-commerce adoption by BUMDES in rural areas. This adoption is expected to have a positive impact on economic development and overall rural progress.